PERAN KEBIJAKAN HUTANG, KEBIJAKAN DEVIDEN, RASIO KEBANGKRUTAN TERHADAP NILAI PERUSAHAAN - Lestari, Rindu Ferdina; Munawaroh, Azizatul (Taksasila Edukasi Insani, 2023)
This research aims to explore the role of debt policy, dividend policy and bankruptcy ratio on company value, especially in telecommunications companies during the period 2019 to 2022. The sampling method used was purposive sampling, and data analysis was carried out using SPSS version 20 software. The main findings of the research these are the three key points. First, the debt policy variable –DER (X1) has an influence on company value. Based on the research, it was found that the DER regression coefficient was -16,698, the t value had a negative sign of -.737, with a significant value of 0.468 which was greater than 0.05 (0.468 0.05), where debt policy had no influence on company value. Second, DPR dividend policy variable (X2). Based on research, the DPR regression coefficient is -2.245, the t value has a negative sign of -3.297 with a significance value of 0.003 which is greater than 0.05 (0.030.05), where DER (X2) has a negative and significant influence on the value of the company. In other words, if the DER value decreases, the company value will increase. The three Bankruptcy Ratio variables (Z-Score)(X3) have a positive value of 443,349, the calculated t value has a positive sign of 2.630, with a significance value of 0.015 which is smaller than 0.05 (0.015 0.05), where the Z-Score (X3) has a positive and significant influence on company value. In other words, when the Z-Score increases, the company value will increase or be in the same direction. These findings are expected to provide important insights for stakeholders to understand the dynamics between these factors in the context of the telecommunications industry. Keywords : Debt policy, dividends, financial distress, market capital